Analisis Kearifan Lokal Melalui Ikan Mas Di Dalam Perayaan Budaya Dan Ritual Keagamaan Etnis Batak - Nerisa Sertiawan; Nuriza Dora (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This research analyzes and examines the local wisdom contained in the arsik carp dish, as well as how this dish has become a central element in cultural celebrations and religious rituals in the Batak ethnic community. In this research, the aim is to describe and understand the arsik carp in cultural celebrations and religious rituals of the Batak ethnic group. Goldfish have a symbolic role that reflects traditions, beliefs and values passed down from generation to generation. In this research, the researcher used a qualitative approach with an ethnographic method, because the ethnographic method examines the role of arsik carp in cultural celebrations and religious rituals in the Batak ethnic group, which is part of the traditions and culture of the Batak ethnic group. The results of this research illustrate that arsik carp is not only a delicious culinary delight and traditional ceremony, but is also used for weddings, seven-month events, post-natal events and can be used to graduate from school or get a new job which is symbolic in connecting the Batak community with its culture. Apart from that, arsik goldfish also have cultural meaning with the symbolism of abundance and good luck in Batak tradition.